Wastewater from the production of lactic acid bacteria as feedstock in anaerobic digestion. (15th August 2021) - Vasmara, Ciro; Marchetti, Rosa; Carminati, Domenico
Abstract: In this study, the biogas production from two fermentation wastewaters deriving from the cultivation of two strains of lactic acid bacteria on ricotta cheese exhausted whey was evaluated in mono-digestion or co-digestion with pig slurry. Lactic acid bacteria were: Lactococcus lactis subsp. l actis and Streptococcus thermophilus . Anaerobic digestion was carried out in laboratory mesophilic, batch, static conditions. Biogas production was monitored until exhaustion. Methane yield of the fermentation wastewaters in mono-digestion was, on average, 372 mL CH4 g −1 VS, and 416 mL CH4 g −1 VS in co-digestion. These values are comparable with that of other feedstocks currently used for biogas production. The co-digestion halved the duration of anaerobic digestion. The fermentation wastewaters are suitable feedstocks for biogas production, and it is possible to directly mix them with pig slurry in existing plants. The digestate could be used as crop fertilizer from a renewable source. Graphical abstract: Image 1 Highlights: CH4 was produced from fermentation wastewater of lactic acid bacteria. CH4 yields were in line with those of other feedstocks used for biogas production. Fermentation wastewaters could advantageously co-digested with pig slurry. Co-digestion has halved the duration of anaerobic digestion, increasing CH4 yield. Digestate from anaerobic digestion could be used to fertilize food/feed crops.